High-Intensity Interval Training Outperforms Fartlek and Continuous Training in Aerobic and Running-Mechanics Adaptations: Evidence from Athletics Education - Wulandari, Fifit Yeti; Pambudi, Nafisa Arif; Jatmikanto, Riski Septa; Hafidz, Abdul; Fajar, Muhammad Kharis; Daulay, Dio Alif Airlangga; Widohardhono, Rachman; Andriana, Laily Mita; S, Adi (Physical Education Theory and Methodology, 2026)
Background. Aerobic capacity and biomechanical efficiency are central determinants of performance in athletics. However, empirical evidence directly comparing different training modalities using an integrative assessment of physiological, biomechanical, and cardiovascular recovery variables remains limited, particularly within structured athletics training environments. Objectives. This study aimed to compare the effectiveness of Fartlek, High Intensity Interval Training (HIIT), and Moderate Continuous Training (MCT) on aerobic capacity, running efficiency, and cardiovascular recovery in sports science students enrolled in athletics courses, thereby providing novel insight into evidence-based conditioning strategies relevant to athletics training. Materials and Methods. A total of 102 sports science students taking athletics coursework were randomly assigned to HIIT (n = 34), Fartlek (n = 34), or MCT (n = 34). The eight-week intervention consisted of three weekly sessions. Measured outcomes included VO₂max, vVO₂max, running economy, stride mechanics, and heart rate recovery (HRR1–HRR3). Data were analyzed using paired t-tests, one-way ANOVA, LSD post-hoc tests, and effect size calculations (Cohen’s d; partial η²). Results. All training models produced significant improvements across all parameters (p < 0.001). HIIT yielded the most substantial gains in VO₂max, vVO₂max, running economy, stride length, ground contact time, and HRR indices. ANOVA revealed significant between-group differences on all primary variables (p < 0.001; η² = 0.27–0.47), indicating the superior adaptive response of HIIT compared with Fartlek and MCT in the athletics training context. Conclusions. The findings confirm that HIIT showed the greatest enhancements in aerobic capacity, mechanical running efficiency, and cardiovascular recovery among the training methods examined in this cohort of sports science students. Its superiority stems from structured high-intensity stimuli that maximize cardiovascular stress, mitochondrial adaptation, lactate tolerance, and neuromuscular recruitment. Further research should investigate responses in competitive athletes, extend intervention duration, and incorporate advanced metabolic and neuromuscular analyses to deepen understanding of HIIT-driven adaptations in athletics.